Neurofeedback effects on cognitive performance in children with attention deficit (2018)
The objective of this research was to analyze the effects of an intervention program through neurofeedback, on the cognitive performance in children with inattention indicators. A quasi-experimental pretest-posttest study was used under a positivist epistemology, with a comparative analysis for each evaluated cognitive process. A sample of 29 cases was intentionally selected from a group of children and young adolescents with low performance indicators from a Therapeutic Center from Cucuta-Colombia. The neurofeedback program was developed in 20 sessions with the purpose of increase low-beta waves (12-16 Hz) and inhibition theta waves (4-7 Hz). A comparative statistically analysis with five months of difference was carried out using Wilcoxon test, finding significant differences between the pretest and the posttest in neuropsychological tests of auditory-visual attention, encoding memory and planning. The results are discussed with empirical backgrounds that have shown positive effects in this type of interventions.